Manajemen Program Center of Excellence (CoE) dalam Meningkatkan Keahlian Penerjemah Bahasa Arab - Anisatin, Luthfi; Abidin, Munirul; Syuhadak, Syuhadak (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
The purpose of this study is to describe the management of the Center of Excellence (CoE) program initiated by the Arabic Language Education Study Program of the University of Muhammadiyah Malang in an effort to improve the skills of Arabic translators. Data collection techniques are interviews and documentation. Data analysis techniques between data collection, data reduction, data presentation, and conclusions. The results of the study found that: first, at the planning stage, the Study Program collaborated with several industrial partners (DUDI) through an MoU, which then collaborated in the preparation of the curriculum, and pre-internship activities. Second, the implementation stage is divided into two main activities, namely translation in written and oral form. Third, the evaluation / assessment stage consists of two main components, namely the value given by the institution where the internship is and the value of the internship supervisor. Through this program, the internship report is used as the equivalent of the thesis.